The influence of muscle strength and aerobic fitness on functional recovery in professional soccer players - Abbott, W.; Clifford, T. (The Journal of Sports Medicine and Physical Fitness, 2022)
BACKGROUND: Well-developed physical qualities may protect athletes from exercise-induced muscle damage and accelerate recovery following exercise. This study examined the influence of muscle strength and aerobic fitness on recovery from competitive soccer matches. METHODS: Fourteen players from the English Premier League 2 (age 18±1 years; height 1.78±0.54 m; mass 73.8±6.3 kg) were equally divided (median split) into a higher or lower group for muscle strength and aerobic fitness, according to their isometric mid-thigh pull (IMPT) and maximal aerobic speed test (MAST) scores, respectively. The following markers of recovery were assessed before (48-h prematch), 12 h (M+1), 36 h (M+2) and 60 h (M+3) after ~3 matches: countermovement jump height (CMJ), reactive strength index (RSI), muscle soreness (DOMS) and wellbeing. RESULTS: IMTP was positively correlated with the recovery of CMJ, RSI and DOMS following matches (P<0.05). In the high IMTP group, DOMS was lower at M+1 to M+3 (all P=0.002; ES=2.10), CMJ was =4% greater at M+1 to M+3 (all P=0.001; ES=2.21) and RSI was =3% higher at M+2 and M+3 (all P=0037; ES=1.25). Players in the H-MAST group did not recover quicker for any variable (all P>0.05). CONCLUSIONS: This study showed that stronger players recovered quicker after matches and highlights the importance of lower-body strength training for soccer players.